2021
DOI: 10.1186/s40364-021-00282-z
|View full text |Cite
|
Sign up to set email alerts
|

Current and emerging therapies for primary central nervous system lymphoma

Abstract: Primary central nervous system (CNS) lymphoma (PCNSL) is a rare type of extranodal lymphoma exclusively involving the CNS at the onset, with diffuse large B-cell lymphoma (DLBCL) as the most common histological subtype. As PCNSL is a malignancy arising in an immune-privileged site, suboptimal delivery of systemic agents into tumor tissues results in poorer outcomes in PCNSL than in non-CNS DLBCLs. Commonly used regimens for PCNSL include high-dose methotrexate-based chemotherapy with rituximab for induction th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 126 publications
0
25
0
Order By: Relevance
“…In the NCCN guidelines, the options for such patients include systemic chemotherapy, radiotherapy with or without chemotherapy, or high-dose MTX therapy with stem cell rescue. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the NCCN guidelines, the options for such patients include systemic chemotherapy, radiotherapy with or without chemotherapy, or high-dose MTX therapy with stem cell rescue. 8 …”
Section: Discussionmentioning
confidence: 99%
“…High-dose methotrexate, other systemic chemotherapy, and stem cell therapy are also considered options. 8 …”
mentioning
confidence: 99%
“…Based on the limited number of studies, dose-reduced WBRT seems to be less toxic than non-reduced dose WBRT in terms of neurologic functional impairment [71,72], and demonstrated a similar response to ASCT [73]. Currently, up to 36 Gy of WBRT with a boost to gross disease to a total of 45 Gy is recommended to the patients who achieve less than CR in systemic induction therapy [1,74].Therefore, for PCNSL patients who get CR/CRu but cannot tolerate ASCT treatment, dosereduced WBRT (< 23.4 Gy) can be considered as one of the consolidation therapeutic strategies, given the balance of neurotoxicity and treatment effectiveness [74]. However, there is no study directly comparing dosereduced WBRT and ASCT on treatment effect and AEs.…”
Section: Consolidation Therapymentioning
confidence: 99%
“…Primary central nervous system lymphoma (PCNSL) is one type of extra-nodal non-Hodgkin lymphoma (NHL), where involvement is restricted to the brain, spinal cord, cranial nerves, leptomeninges and vitreo-retina [1,2]. It is a relatively rare tumor, accounting for about 1% of NHLs and 3-4% of intracranial tumors [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, other biological factors or molecular characteristics of tumors have been identified. For example, it has been reported that high protein levels of interleukin (IL)-10 at diagnosis or co-expression of MYC/BCL2 in tumors correlate with low overall survival (OS) and progression-free survival (PFS) [ 56 , 57 ]. In addition, many prognostic factors have been proposed in MRI, including multifocal lesions, high tumor volume, or subtentorial involvement, but with controversial results [ 58 , 59 ].…”
Section: Brain Imaging Features At Diagnosismentioning
confidence: 99%